Feminino e subjetividades: as personagens femininas como elemento de coesão em Corpo de Baile - Cazarotto, Cleide Aparecida de Souza (2022)
Our approach to the work Corpo de Baile, by João Guimarães Rosa, is based on the female characters and the various facets of subjectivity and, as a goal, to evidence from these characters the unity links of the work. Despite the female performative diversity, there are very close goals that can be synthesized as humanity. In fact, given the socio-historical context of Rosa's work, that is, the Minas Gerais hinterland and patriarchal society, the prominence is male, however, such characters, said to be main ones, are notably incomplete, which gives the plots their believable character; that is, they present the peculiar pertinence of “real human beings”. It should be added that the support for such incompleteness, as a rule, is the female in her various roles - mothers, wives, lovers, friend, etc. Within this reality, the role of the feminine could be taken as of little or no relevance. A careful look shows, however, that women are participants in masculine paths and, in this way, act as a cohesive element, both social and individual. In Rosa's fictional construction, women are references for the thought, speech and actions of male characters, although the female group is not homogeneous, on the contrary, the author presents two large groups, the feminine-maternal and the feminine-desire, and between one and the other, the poetic imaginary in the form of an “ethereal bride”. In order to high light the lack of standardization of behavior based on subjectivity, the theoretical corpus of the thesis covered the concept sarising from the Philosophy of Language, Theory of Enunciation and Psychoanalysis